Seeking Out High Risk Population: The Prevalence Characteristics and Outcome of Diabetic Patients of Arab Ethnicity Hospitalized in Internal Medical and Acute Coronary Units in Israel. (17th June 2013) - Nseir, William; Haj, Shehadeh; Beshara, Basma; Mograbi, Julnar; Cohen, Ohad
Abstract : Aims . To seek high risk population for diabetes and to improve their health care by investigating the characteristics and outcome of hospitalization in hospitals with predominant Arab patients in Northern Israel. Methods . Retrospective analysis of the prevalence of diabetes and the outcome of diabetic in comparison to nondiabetic patients hospitalized in the internal medicine and intensive cardiac units in two major hospitals with one-year postdischarge data between 1.1.2009 and 31.12.2009. Results . Thirty-nine percent of the patients were diagnosed with diabetes. The preponderance of women in the diabetes group was noted. Diabetic patients had an increase in the duration of hospitalization (P = 0.0008 ), with one hospital having a high readmission rate for the diabetic patients. The average glycemia during hospitalization exceeded the recommended threshold of 180 mg% without major changes in the therapeutic regimens in comparison to preadmission regimens. Conclusions . Arab populations, women in particular, in westernizing societies are at high risk for diabetes which exemplifies as high rate of patients with diabetes among hospitalized patients. Areas for intervention during hospitalization and at predischarge have been identified to improve health outcomes and prevent readmissions.